Genetically Modulated Substrate Reduction Therapy for Sanfilippo syndrome – proof of principle - Santos, J.I. (2021)
Introduction: Mucopolysaccharidosis type III (MPS III) refers to a group of five autosomal recessive neurodegenerative lysosomal storage disorders caused by the incomplete lysosomal degradation of the heparan sulphate (HS) that accumulates in patient cells and triggers disease. The main characteristic of this disease is the degeneration of the central nervous system, resulting in mental retardation and hyperactivity. Currently, there is no effective therapy available, with treatment limited to clinical management of neurological symptoms. Methods: Taking advantage of the RNA interference (RNAi) technology potential, we have designed and assayed a specific siRNA targeting an early stage of the HS biosynthetic cascade (XYLT1) in order to promote an effective reduction of the accumulating substrate. Fibroblasts from MPS III patients were transfected with the designed siRNA. Total RNA was extracted and target mRNA levels evaluated through real-time PCR. The effect on GAGs accumulation was quantified over time using a modified 1,9-dimethylmethylene blue assay. Results: Proof of principle on the effect of siRNA targeting XYLT1 was achieved for two independent control cell lines, with 8-12 fold decreases on the target mRNA levels, after 24h of incubation with concentrations of 20nM of each siRNA. Subsequent analysis on the effect of the same siRNA on MPS III cell lines resulted in significant lower expression of XYLT1 in types A, B and C, after 24-48h of siRNA incubation. Studies on type B are also ongoing. For types C and D, we have already assessed the treatment effect on storage and observed a significant reduction (50-70%) on the total GAGs levels. Conclusions: The effect of siRNA targeting XYLT1 was achieved, resulting in significant lower levels of XYLT1 mRNA. Studies on MPS IIIB are ongoing. Moreover, a significant reduction on GAGs’ accumulation was observed, and we are currently addressing this storage in the remaining MPS III cell lines.